Heavy alcohol consumption among marginalised African refugee young people in Melbourne, Australia: motivations for drinking, experiences of alcohol-related problems and strategies for managing drinking - Horyniak, D.; Higgs, Peter; Cogger, S.; Dietze, P.; Bofu, T. (Emerald Group Publishing Limited, 2016)
Objective. Little is known about substance use among resettled refugee populations. This study aimed to describe motivations for drinking, experiences of alcohol-related problems and strategies for managing drinking among marginalised African refugee young people in Melbourne, Australia. Design. Face-to-face interviews were conducted with 16 self-identified African refugees recruited from street-based settings in 2012–2013. Interview transcripts were analysed inductively to identify key themes. Results. Participants gathered in public spaces to consume alcohol on a daily or near-daily basis. Three key motivations for heavy alcohol consumption were identified: drinking to cope with trauma, drinking to cope with boredom and frustration and drinking as a social experience. Participants reported experiencing a range of health and social consequences of their alcohol consumption, including breakdown of family relationships, homelessness, interpersonal violence, contact with the justice system and poor health. Strategies for managing drinking included attending counselling or residential detoxification programmes, self-imposed physical isolation and intentionally committing crime in order to be incarcerated. Conclusion. These findings highlight the urgent need for targeted harm reduction education for African young people who consume alcohol. Given the importance of social relationships within this community, use of peer-based strategies are likely to be particularly effective. Development and implementation of programmes that address the underlying health and psychosocial causes and consequences of heavy alcohol use are also needed.